National Insurance Act, 1911 (leaflet) (London : National Health Insurance Commission (England))
1912-06 1912 1910s 4 pages N.H. Leaflet. NATIONAL INSURANCE ACT, 1911. NATIONAL HEALTH INSURANCE COMMISSION (England), Buckingham Gate, London, S.W. June, 1912. THIS ACT WILL COME INTO FORCE ON— MONDAY, JULY, 1912. THE NATIONAL HEALTH INSURANCE COMMISSION give notice that, with certain exceptions (see page 2) :— EVERY PERSON IN THE SERVICE OF AN EMPLOYER must be insured, if between the ages of 16 and 70, and must— 1. GET A CONTRIBUTION CARD before 15th July, either from the Approved Society of which he or she is a member, or from any Post Office; and 2. PRODUCE IT TO HIS OR HER EMPLOYER before 15th July, to be stamped on the first pay day. N.B.— The Full Benefits of Insurance can only be obtained by Joining an Approved Society. (See page 4.) (For Rates of Contributions and Benefits, see page 3.) This concerns every employed person. EVERY EMPLOYER must— 1. REQUIRE CONTRIBUTION CARDS from every person in his employment (unless excluded under A, page 2) ; or, if the employed person fails to produce a card, use an Emergency Card which may be obtained from any Post Office ; 2. OBTAIN HEALTH INSURANCE STAMPS at the Post Office: and 3. STAMP THE CARDS before paying wages. PENALTIES.— The Penalty for each Offence against the Act or the Regulations made under the Act is a fine not exceeding TEN POUNDS. This concerns every Employer. [Further copies of this Leaflet and a Memorandum for Employers (Pamphlet A) will be supplied at any Post Office or by any of the Customs and Excise Officers, whose addresses may be obtained at the Post Office. (M2082) Wt.7106-315 4,000M 6/12 H&S. 345/3/2/1